The structure and mechanical properties of Cu50Ni50 alloy nanofoams formed via polymeric templating. (June 2020) - Kim, Chang-Eun; Rahimi, Raheleh M.; Bahr, David F.
Abstract: Abstract : The authors demonstrate that multicomponent metallic alloy nanofoams can be synthesized by the polymeric templating method. The present approach enabled alloy compositions not accessible via commonly used dealloying or co-deposition methods. The authors report the synthesis of a Cu50 Ni50 alloy nanofoam using electrospinning polymeric templating, which exhibits distinct polycrystallinity, process-driven segregation, and enhanced mechanical strength over pure Cu nanofoams. Transmission electron microscopy revealed microscopic grain formation and their variable compositions. The processing method is applicable to the synthesis of a wide range of multicomponent metal porous materials, creating new research opportunities for noble alloy foams not available through wet electrochemical routes.